6-Fold path to self-forgiveness: an interdisciplinary model for the treatment of moral injury with intervention strategies for clinicians - DeMarco, Michele J. (Frontiers in Psychology, 2024)
Conscience is the indestructible core of one's personal identity and their sense of agency in the world. When it passes judgment against them, it generates inner conflict (i.e., moral injury). At its core, moral injury is about trust and sacred relationships, particularly the loss of safe connection with self, society, God/Divine/a Higher Power, and the world. The clash between a person's conscience and overwhelming existential or psychospiritual experiences, which uniquely defines moral injury, alienates them from life-sustaining relationships. Healing requires more than reordering fractured belief systems. Reestablishing bonds of self-worth, trust, and lifesustaining relationships are essential. This paper presents The 6-Fold Path to Self-Forgiveness (6-FPSF), an interdisciplinary, narrative-based healing writing process for the treatment of moral injury, particularly self-induced moral injury. Self-forgiveness has been associated with psychospiritual and relational well-being. The protocol draws upon theoretical literature, evidence-based psychological interventions, spiritual-oriented practices, creative arts, and somatic exercises for mental health counseling and spiritual/religious ministration. In addition to describing the 6-component therapeutic model, the author offers intervention strategies for clinicians.